A Proactive, Systematic Approach to Building the Capacity of Technical Assistance Providers. Issue 3 (May 2023) - Kenworthy, Tara; Domlyn, Ariel; Scott, Victoria C.; Schwartz, Randy; Wandersman, Abraham
Technical assistance (TA) is a major capacity building strategy used by the government sector to promote health outcomes in the United States. However, there is minimal literature about how to develop TA provider capacities. This article describes a systematic and proactive approach for developing TA provider capacity, referred to as Technical Assistance for Technical Assistance Providers (TAFTAP), which draws on three implementation science frameworks (Interactive Systems Framework for Dissemination and Implementation, Getting To Outcomes, and R = MC 2 ). We present an application of TAFTAP within a federal agency providing a readiness-informed TA approach to health departments of states, territories, and tribal areas implementing comprehensive tobacco prevention control programs. Pilot data suggest that TAFTAP is a promising approach for improving the quality of TA delivery. At the end of the 2-year project period, TAFTAP recipients provided generally positive qualitative feedback about the support they received. They chose to sustain the readiness-informed TA by incorporating it into a future funding announcement. Downstream state-level TA grantee recipients reported positive outcomes (e.g., accelerated progress, enjoying more one-on-one time with TA providers) from receiving the TA innovation from TAFTAP recipients. We suggest that funding agencies and training and TA centers consider this approach to bolster the capacity and motivation of TA providers for downstream benefit to health and human services staff and their clients. Practical steps for employing TAFTAP to advance health outcomes are included in this article.